Synthesis, Characterization and Antimicrobial Studies of Novel Binuclear Transition Metal Complexes of Schiff Base Derived from 1-Amino-5-methyl-2,6-pyrimidine-dione and 2,3-Butanedione - Pal Singh, Netra; Nanda Srivastava, Abhay (Asian Journal of Chemistry, 2012)
A series of binuclear transition metal complexes of the type [M2(L)2X4)]·nH2O (where, M = Cu(II), Ni(II), Co(II) or Zn(II), X= Cl–/CH3COO– and L = ligand) of a Schiff base ligand derived from 1-amino-5-methyl-2,6-pyrimidine-dione and 2,3-butanedione have been synthesized and characterized by elemental analysis, molar conductance measurements, magnetic moment measurements, IR, UV-visible, 1H NMR, EPR and mass spectral studies. Electronic spectral data and magnetic moment values indicate octahedral geometry for all the metal complexes. In vitro antimicrobial activity of ligand and its metal complexes were also studied against bacteria (Bacillus subtilis and Escherichia coli) and fungi (Aspergillus niger and Aspergillus flavus) which show antimicrobial activity of ligand and binuclear metal complexes.